A imagética das beatitudes em Hieronymus Bosch: religiosidade popular na cristandade medieval e no renascimento do norte europeu – séculos XIV-XVI - Sousa, Radamés de (2021)
propose a narrative interpretation running through flemish religious iconography between the 15th and 16th centuries, through the forms of religious experience of the saints, hermits, monks and preachers that were disseminated in that period and that the iconography portrayed so richly. I will analyze the influence of saints, hermits, martyrs on popular christian religiosity through primary sources that constituted a primordial basis for artisticreligious creations, established of biblical, hagiographic origin or even of medieval bestiaries. I will treat, as the main focus of this analysis, the pictorial set of Hieronymus Bosch (1450-1516), but also other artists from his surroundings who portrayed, through religious iconography, their views of the types of religious life. And through theoretical and methodological support, such as the concept of holiness proposed by the medievalist historian André Vauchez (1989), by the study of historian Johan Huizinga (1872-1945) on devotion in the Autumn of the Middle Ages and by the most recent works of historians of art that they analyze about the pictorial set of Hieronymus Bosch, namely, Lynn F. Jacobs (2000), Stefan Fischer (2014), Matthijs Ilsink (2016), Walter Bosing (2006). Finally, use the iconological method of image analysis proposed by Erwin Panofsky (1991) for this research.